CONTAMINATION OF THE HANDLES AND BASES OF SHOPPING CARTS BY PATHOGENIC AND MULTI-DRUG RESISTANT BACTERIA - Irshaid, Fawzi I.; Jacob, Jacob H.; Khwaldh, Alia S. (European Scientific Journal, ESJ, 2014)
Background and Aims: Shopping carts (SCs) are considered as highly contaminated public surfaces, and may play a role in transmission of some harbor heterotrophic bacteria to human being. Therefore, this study aimed to examine the hygienic conditions and presence of heterotrophic bacteria on the surface of the handles and bases of SCs taken from shopping stores in Al-Mafraq city, Jordan. Methods: Five different SCs were selected randomly from four shopping stores (designated as A, B, C and D) during May through June, 2011. Two dry swab samples were taken from each SC, one from the handle and another one from the base. All samples were cultured on nutrient agar as none selective medium and incubated aerobically at 37 °C for 48 hours. The resulting number of colony forming units (CFUs) in each plate was converted to CFU per cm2 surface area. The species of bacterial isolates were determined by biochemical tests and 16S rDNA sequencing. Results: The number of heterotrophic bacteria per SC range between 6 to 133 CFU/cm2 surface area for the cart handles and between 6 to 300 CFU/cm2 surface area for the cart bases, indicating higher numbers of heterotrophic bacteria in the cart bases as well as more fluctuations in the number of heterotrophic bacteria at the handles and bases of SCs. These analyses also confirmed the presence of seven coliform and three noncoliform species on the tested surface of the handles and bases of the selected stores. These include E. coli spp., Acinetobacter calcoaceticus, Burkholderia cepacia, Yersinia enterocolitica, Tatumeella ptyseas, Pseudomonas aeruginosa, Shigella sonnei, Bacillus cereus, and Bacillus pumilus. Conclusion: The resulting data revealed that some of these species are pathogenic as well as a multi-drug resistant. These data also indicated that poor sanitation and hygiene conditions appear to exist among the tested SCs of the selected stores. It also suggest that these SCs might act as source of transmitting of pathogens which might pose a serious health risk to shoppers. Therefore, this study pleads for a strong cleaning approaches for SCs as well as community education to promote hand hygiene, both of which are important and complementary.